2002
DOI: 10.1080/03601270290099822
|View full text |Cite
|
Sign up to set email alerts
|

Opinions of College Students and Independent-Living Adults Regarding Successful Aging

Abstract: This study compared opinions of successful aging among college students and older independent-living adults. Participants were 226 undergraduate students, 44 graduate students, and 59 independent-living older adults subjects. The participants were asked to rate the level of importance of 29 items in relation to their contribution to successful aging. The 29 items were divided into seven categories. Social and familial relationships, intrinsic values, nancial concerns, accomplishments, and cognitive functioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 8 publications
(2 reference statements)
1
18
0
1
Order By: Relevance
“…Financial security was found to be important across all age bands in Charbonneau-Lyons et al ’s study,27 in all permutations of gender, education and income, aside from females in the no/low education/income group in Nagalingam's study,28 and by all the respondents in the study by Lin 29. Environment and finances are typically excluded from current models3 30 and the identification of these factors in such a large number of studies is therefore a unique finding.…”
Section: Discussionmentioning
confidence: 76%
“…Financial security was found to be important across all age bands in Charbonneau-Lyons et al ’s study,27 in all permutations of gender, education and income, aside from females in the no/low education/income group in Nagalingam's study,28 and by all the respondents in the study by Lin 29. Environment and finances are typically excluded from current models3 30 and the identification of these factors in such a large number of studies is therefore a unique finding.…”
Section: Discussionmentioning
confidence: 76%
“…The few, published investigations of lay views of successful ageing have indicated that they are far more multi-domain than existing theoretical models, crossing the boundaries between the physical, psychological and social self (Fisher 1992(Fisher , 1995Fisher and Specht 1999;Guse and Masesar 1999;Bergstrom and Holmes 2000;Von Faber et al 2001;Charbonneau-Lyons et al 2002;Knight and Ricciardelli 2003;Tate et al 2003;Phelan et al 2004;see Bowling and Dieppe 2005). However, not all of these studies asked older people for their own views, with some asking people simply to rate researchers' definitions (Phelan et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It was not possible in this review to place studies in hierarchical order of methodological quality, due to the wide range of approaches used (qualitative and quantitative); lack of clarity over actual sample sizes especially where longitudinal surveys, and also nested case study approaches, were reported; differences in sizes, and types of samples (e.g., males only (Crosnoe & Elder, 2002;Vaillant & Mukamal, 2001), socially or educationally advantaged samples (e.g., Charbonneau-Lyons et al, 2002;Crosnoe & Elder, 2002;Palmore, 1979;Perls & Silver, 1999), occupation-specific cohorts and samples (Abraham & Hansson, 1995;Tate et al, 2003), samples biased toward healthier population members (Havighurst, 1957;Palmore, 1979;Williams & Wirths, 1965), members of organizations for older people (Everard et al, 2000), and in some cases lack of information about the area of the survey. Nor was it possible to compare and rank studies by the strength of their evidence, given that investigators defined successful aging largely in terms of their own disciplines, often using the concept uncritically, with the consequence that their findings reflected their definitions and measures in isolation from the broader literature.…”
Section: Resultsmentioning
confidence: 99%